Optimalisasi Keterampilan Literasi Digital melalui Model Pembelajaran Flipped Classroom - Anggi Diva Safira; Dewi Fatimah Az Zahra; Faujiyah Rahma; Farida Fauziah; Iwan Ridwan Yusup (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
The development of information technology requires that it is important for every individual to have digital literacy skills as a competency in facing the challenges of advancing globalization. Education is a means of improving digital literacy skills, one of the efforts made is through implementing the flipped classroom learning model in learning activities. This research aims to further explore the effectiveness of the flipped classroom model in increasing digital literacy in biology learning. The research was conducted on a sample of 28 Class XI MIPA 2 students at SMA Mekar Arum Cileunyi, Kab. Bandung. Data were collected using a pretest-posttest in the form of 10 essay questions on the Circulation System material, then the results obtained were tested statistically. In this study, it was found that there was an increase in positive ranks from the pretest and posttest results in the non-parametric Wilcoxon Signed Rank statistical test where the Z value, namely -4.631b, was smaller than 0.05 so that H0 was accepted. So it can be concluded that the flipped classroom learning model has an effect on digital literacy skills.